REPRESENTASI PEREMPUAN DALAM MEDIA AUDIOVISUAL DI INDONESIA - Muliawati, Ditha; Pradekso, Tandiyo; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2024)
The representation of female in media is an intriguing topic to explore due to the significant influence media has in shaping these representations. This article highlights the substantial differences in the portrayal of female across movie cinemas, television series, and video-on-demand (VoD) services. In examining the development of female's representation in Indonesian cinema over the past few years, there is a noticeable improvement compared to the early periods of movie cinema development in Indonesia. The presence of female directors has enhanced the quality of female's representation in movies, challenging the dominance of masculinity and patriarchal narrative. In contrast to movie cinemas, the television series (sinetron) industry remains entrenched in patriarchal narratives when depicting female on screen. Indonesian television series/soap operas are heavily influenced by the New Order's concept of femininity, which marginalizes female. Even during the 2000s, a period marked by the proliferation of sinetron, the themes became increasingly unrealistic due to the demands of continuous production (sistem kejar-tayang), resulting in unclear storylines. With the rapid growth of the Video on Demand (VoD) industry, including platforms such as Netflix, Vidio, Viu, WeTV, Disney+ Hotstar, Iflix, and HOOQ, feminist narratives have gained more prominence in Indonesian media consumption. Major subscription video on demand (SVoD) platforms like Disney+ and Netflix are committed to promoting narratives of inclusivity and diversity in their content, whether in movies or series formats.